1982
DOI: 10.1111/j.1365-2621.1982.tb10134.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Iron Produced by the Corrosion of Steel in Apples

Abstract: The bioavailability of iron formed by the corrosion of low-carbon steel (99% Fe) in contact with Red Delicious apples was measured in a rat model using a depletion-repletion experiment. The percentage of ingested iron converted to hemoglobin iron (Conversion Efflciency) was 74, 57, and 56%, respectively, for daily doses of 110, 190, and 285 pg of this iron. (Conversion Efficiency for FeS04 was 46-50%). When compared with FeS04 = 100, the relative biological value of this iron was found to range from 93-153. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The iron content of foods cooked in iron utensils increases significantly [3][4][5]. The bioavailability of iron from apples with nails inserted to rust [6] and from food cooked in iron pots [7] is relatively high.…”
Section: Introductionmentioning
confidence: 99%
“…The iron content of foods cooked in iron utensils increases significantly [3][4][5]. The bioavailability of iron from apples with nails inserted to rust [6] and from food cooked in iron pots [7] is relatively high.…”
Section: Introductionmentioning
confidence: 99%
“…Very little is also known about the bioavailability of the various forms of contaminating iron. However, there have been recent attempts to quantitate this problem (Hallberg and Bjorn-Rassmusen, 1981;Hallberg et al, 1983;Rosanoff and Kennedy, 1982). Amine et al (1972) have also shown that the extrinsic tag technique will not give an accurate measurement of iron absorption from a diet which contains insoluble iron.…”
mentioning
confidence: 99%
“…On the background of studies showing a possibility of a significant rise in haemoglobin values in humans from the intake of food exposed to iron cookware Rosanof and Kennedy investigated the bioavailability of iron produced by the corrosion of low-carbon steel (99%) in contact with Red Delicious apples [34]. A high percentage of the ingested iron was converted into haemoglobin iron, and ingestion of one Red Delicious apple that had been exposed to eight large iron nails for 24 h could provide 10 -15 mg having good bioavailability.…”
Section: Applesmentioning
confidence: 99%